1995
DOI: 10.1007/bf02369785
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic strength in oriented fiber glass composite shells

Abstract: 624.074.4:678 Differences in chemical compositions and mechanical properties of fibers and different schemes of layer reinforcement of composite shells pose the problem of their optimal choice to ensure high specific strength under dynamic loading (such as for protective constructions of a single action) [1][2][3].The purpose of this paper is to study the dynamic response and the carrying capacity under the internal explosive loading of oriented fiberglass shells reinforced with roving strips based on VM-1,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2005
2005
2005
2005

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(6 citation statements)
references
References 6 publications
0
6
0
Order By: Relevance
“…The experiments of [17] showed that the specific strength distribution according to the criterion ξ under explosive loading completely agrees with the order anticipated according to the criterion w for fibers. The highest specific load-bearing capacity is characteristic of VM-1 and VMP fiberglass shells, and the specific loadbearing capacity of R and Kh fiber shells is 25 and 45%, respectively, lower.…”
Section: Introductionmentioning
confidence: 65%
See 4 more Smart Citations
“…The experiments of [17] showed that the specific strength distribution according to the criterion ξ under explosive loading completely agrees with the order anticipated according to the criterion w for fibers. The highest specific load-bearing capacity is characteristic of VM-1 and VMP fiberglass shells, and the specific loadbearing capacity of R and Kh fiber shells is 25 and 45%, respectively, lower.…”
Section: Introductionmentioning
confidence: 65%
“…The results of similar tests of SHM organic plastic shells are also given in [17] for comparison. Cylindrical shells were formed by combined winding of tapes impregnated withÉDT-10 epoxy binder with alternation of double helical (ϕ 1 = ±45 • ) and hoop (ϕ 2 = 90 • ) layers at a layer thickness ratio of 1 : 1.…”
Section: Introductionmentioning
confidence: 97%
See 3 more Smart Citations